Strength Defined By Speed and Its Relationship with Dribbling Speed in Futsal Players - shameal, wamed (Journal of Physical Education, 2011)
The first chapter included the introduction, problem, aims and hypotheses of the research. The training process includes preparing the players physically, artistically, tactically and psychologically. The key for performance completion is the linking between the physical aspect and all other aspect. The importance of the research lies in linking some physical abilities especially strength defined by speed with the most important skill in futsal which is dribbling. In chapter two, the researcher tackled theoretical and similar studies. The procedures of the research were tackled in chapter three. The researcher selected the descriptive method. The subjects were (10) futsal league players. The researcher conducted a pilot study to identify the validity of the tests then the tests were applied on the subjects of the research. Chapter four included the display, discussion and analyses of the results based on statistical operations. The results showed a significant correlations relationship among the variables understudy. The final chapter; chapter five, tackled many recommendations that the researcher came up with in the light of the results.